An Innovative Rigid Tray Technique as a New Alternative Matrix System for Buildup of Severely Damaged Endodontically Treated Teeth (A Case Report) - Saied Mostafa Moazzami; Hamideh Sadat Mohammadipour; Atefeh Atoufi; Michael Meharry (Mashhad University of Medical Sciences, 2014)
Direct restoration of severely damaged endodontically treated teeth (ETT) using available and conventional and current matrix systems is sometimes impractical and in some clinical cases is impossible. The aim of this paper is to introduce and describe a new matrix system based on Rigid Tray Technique (RTT) for dealing with such difficult clinical cases.